MAESTRO CONDENADO, DISCÍPULO INDIGNADO. LA IMAGEN DE PEDRO ABELARDO Y LA EXASPERADA DEFENSA DE BERENGARIO DE POITIERS (Stylos, 2021)
It is well known that Peter Abelard, the most famous master of the 12th century, knew how to drive mad not only his laic colleagues of urban schools, but also important ecclesiastical leaders. This is confirmed by the two Councils in which Abelard was condemned: Soissons (1121), and Sens (1141). Since the end of the 19th century, rivers of ink have flowed concerning both factual events and grudges, envies, and even the murder conspiracies perpetrated against Abelard. If to this troubling scenario is added the very little reproduction of their works in the years after his death, and the lack of explicit mentions of Abelard’s doctrine done by other medieval authors, it might seem that his image and his ideas are today much better appreciated than they really were in his own time. Nevertheless, it is not the case. We have lots of statements proving Abelard’s reputation in the scholar life of the 12th century. It is not casual that even nowadays medievalists keep referring to him as the Magister par excellence.Then, this paper is dedicated to the passions that Abelard, as master, inflamed among his students. It is divided into two parts. The first one consists in a succinct revision of four particularly suggestive testimonies about his days as a teacher; the second part is focused on an “outraged disciple”, Berenger of Poitiers, and his Apologia Berengarii Pictauensis contra sanctum Bernardum Claraeuallensem abbatem et alios qui condemnauerunt Petrum Abaelardum.
Keywords: Peter Abelard – Berengar of Poitiers – Apologia – Sens.